Professional training of human resources in the context of sustainable development at the level of the Sălaj County Police inspectorate - Roxana Demian (Agora International Journal of Economical Sciences (AIJES), 2024)
This study highlights the changes in human resource management, the shift from traditional paradigms to an individual-centered approach, and the importance of continuous learning and adaptability. It describes the sustainable development of human resources in the Sălaj County Police Inspectorate, emphasizing the crucial role in maintaining public order and cooperation with various institutions, the activity of the structures of the Human Resources Service and the Professional Training Office within the unit, structures with essential activities in the management and development of police personnel. The culmination of the study is the analysis of the professional training within the inspectorate, which highlights the progress and adaptability in the training of the personnel within the Sălaj County Police Inspectorate, but also the importance of effective communication and recognition of meritorious in achieving institutional performance.
Keywords: 330; human resources management; sustainable development; Sălaj County Police Inspectorate; professional training; institutional cooperation; Professional Training Office; police tactics